Pelatihan Bantuan Hidup Dasar Pada Kegawatdaruratan Bayi Saat Tersedak Menggunakan Teknik Chest Thrust di Desa Ledug - Wahyuni, Tika; Sukmaningtyas, Wilis; Hanum NA, Fauziah (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Background: Infants are a population that is vulnerable to health problems. Health problems experienced by infants become emergencies if not handled properly. One of the emergencies that is often experienced by infants is choking. Choking is a condition where a foreign object blocks the throat for various reasons, blocking the flow of air. Handling of infants aged 0-1 years using the chest thrust technique. Objective: This Community Service aims to identify the level of knowledge and skills of pregnant women and mothers who have babies in providing basic life support in the event of a choking baby emergency. Method: This Community Service uses lecture and demonstration methods. Participants who attended and participated in the activity were 25 people. The activity was carried out at the Ledug Purwokerto Village Hall on Friday, September 30, 2024. The media used were in the form of powerpoint, leaflets and videos.  Results: The level of knowledge before education was carried out, 8 participants (32.0%) had insufficient knowledge, 4 participants (16.0%) had sufficient knowledge and 13 participants (52.0%) had good knowledge. Meanwhile, after being given education, 25 participants (100%) were in the good category. The skill level before being given education and demonstration, all participants were unskilled, 25 participants (100.0%). Meanwhile, after being given education and demonstration, 22 participants (65.6%) had skilled skills and 3 people (12.0%) had poor skills. Output: This community service is in the form of leaflets, videos, and journal publications.